2013
DOI: 10.1111/j.1365-4632.2012.05826.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulins in difficult‐to‐treat ulcerated livedoid vasculopathy: five cases and a literature review

Abstract: These cases confirm previous reports that IVIG seems to be a rapid, effective, and safe treatment for patients with idiopathic refractory ulcerated LV. However, a placebo-controlled study is mandatory to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…These patients were successfully treated with IVIG: 94% had at least > 50% improvement with 63% going to complete remission. Our data were concordant with previous studies and justified the use of IVIG as a second-line treatment after unsuccessful use of heparin anticoagulation (16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These patients were successfully treated with IVIG: 94% had at least > 50% improvement with 63% going to complete remission. Our data were concordant with previous studies and justified the use of IVIG as a second-line treatment after unsuccessful use of heparin anticoagulation (16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 91%
“…Most treatments are based on anticoagulation (1,3). Several retrospective studies and case reports have shown a good response to intravenous immunoglobulins (IVIG) in refractory patients (16)(17)(18)(19). However, in the absence of large prospective controlled studies, there is no recommendation on the dose or duration of medication and as such the optimal therapeutic regimen is unknown.…”
mentioning
confidence: 99%
“…There have been three case series of LV treated with IVIg thus far . The results of our series are similar to the previous reports in that three cycles of monthly IVIg was effective and improvement in pain was achieved faster and was more significant compared with erythema and ulceration ( p = 0.041).…”
Section: Discussionsupporting
confidence: 87%
“…[12][13][14][15][16][17][18][19][20][21][22][23][24] A number of therapies have been proposed, including anticoagulant, fibrinolytic, antiplatelet, immunosuppressant, and immunomodulator therapy, as well as hyperbaric oxygen; however, IVIG was felt to be the best option. 12-24 A number of studies supported the use of IVIG in the treatment of LV and demonstrated good outcomes 14,15,[21][22][23] with minimal adverse effects, 24 and it has been shown to benefit those with difficultto-treat LV. 25 These findings led us to initially seek IVIG as a treatment option.…”
Section: Thrombotic Vasculopathy In a Patient With Initially Undetectmentioning
confidence: 99%